Mechanical design of a superconducting demonstrator for magnetic density separation. (14th October 2021) - Kosse, J J; Wessel, W A J; Zhou, C; Dhallé, M; Tomás, G; Krooshoop, H J G; Brake, H J M ter; Kate, H H J ten
Abstract: The focus of this paper is on the mechanical design of a NbTi-based demonstrator magnet for magnetic density separation (MDS) that is being constructed at the University of Twente. MDS is a new recycling technology that allows the separation of non-magnetic particles based on their mass density, using a vertical magnetic field gradient and a ferrofluid. The unique mechanical design challenge for this type of magnet is the desired minimization of the distance between a sim1 m 2 planar array of cryogenic racetrack coils and the ambient-temperature ferrofluid bath. The optimization of the magnet geometry results in a distance between the coils and ferrofluid of 50 mm. This is made possible by opting for conduction-cooling, for the inclusion of room-temperature rods that pass through the cold mass to support the cryostat, and for the geometry of the cassette that reacts to the Lorentz force.